The use of body surface temperatures in assessing thermal status of hutch-reared dairy calves in shaded and unshaded conditions - Bakony, Mikolt; Kovács, Levente; Kézér, Luca Fruzsina; Jurkovich, Viktor (Frontiers in Veterinary Science, 2023)
The study was carried out in a Hungarian large-scale dairy farm during a 5-day period in hot August weather. Altogether 16 preweaning calves were chosen for the study. An agricultural mesh with 80% shielding was stretched over eight calf cages at 2 m from the ground to shield the cages in their entirety, while eight others were left unshaded. Ambient temperature and relative humidity were measured in 10 min intervals inside and outside one of the hutches in the shaded and unshaded groups during the total length of the study. The rectal temperature of the calves was measured by a digital thermometer every 4 hours. Surface temperatures were measured on body parts, in the same intervals as rectal temperature with an infrared thermometer. Measuring sites included: the leg (metacarpus), muzzle, eye bulb, scapula, and ear. Statistical analyses were performed to assess the effects of shading on environmental and body temperatures and also to assess the strength of the association between core, skin and ambient temperatures; to estimate the temperature gradient between body shell and core; to compare the changes in heat dissipation capacity of the different body regions (as represented by temperatures of various sites) with increasing ambient temperature controlling for shaded or unshaded conditions; and to predict the risk of hyperthermia (rectal temperature not lower than 39.5 °C) with the decision tree algorithm method. The average rectal temperatures suggest that the temperature conditions both in shaded and unshaded groups imposed a severe heat load on the calves. The temperature of the body shell, as represented by skin temperatures, shows a much more significant variation, similar to ambient temperature. As expected, areas that are closer to the core of the body (ear and eye) show less difference from rectal temperature and show a narrower range (lower variance), as more distal regions (leg, scapula) have a wider range. Body surface temperatures are more related to ambient temperature in calves than rectal temperature. The predictive value of infrared body surface temperatures for predicting heat stress or rectal temperature is low.